Gentamicin-sensitivity testing of Burkholderia Pseudomallei clinical isolates from Sarawak - Tan, Pei Chin (Universiti Malaysia Sarawak (UNIMAS), 2016)
Burkholderia pseudomallei is the causative agent for melioidosis disease. Melioidosis is a potentially fatal disease which is difficult to treat due to its inherent resistance to many antibiotics such as aminoglycosides, ~-lactams, macrolides, and polymyxins. Laboratory diagnosis of this disease includes antibody detection, antigen detection, molecular techniques, and also bacterial culture using selective medium. Gentamicin is one of the selective agents utilized in the selective medium as the bacterium is resistant to it. Recently, there was a study which discovered that there were gentamicinsensitive mutant clinical strains from central Sarawak. Hence, this study was conducted in order to do preliminary test for gentamicin-susceptible clinical B. pseudomallei strains from Sarawak. Antibiotic susceptibility test was carried out using disk diffusion tests to identify the gentamicin sensitivity properties of 112 B. pseudomallei clinical isolates collected from selected Sarawak district hospitals. The finding of this study indicates that the prevalence of gentamicin sensitivity of the isolates tested is 76 %. This preliminary study result plays a crucial role in the first phase as to support continuous surveillance ofgentamicin-susceptible B. pseudomallei strains in Sarawak. This will prevent misdiagnosis of melioidosis cases which then reduce potential errors in antibiotics therapy and possible deaths.